Efektivitas Pijat Punggung Atas terhadap Tekanan Sistol Diastol Ibu Hamil Trimester III di RSUD Kota Cilegon Tahun 2024: Effectiveness of Upper Bac Massage on 3rd Trimester Pregnant Women’s Diastal Systolic Pressure in Hospital Cilegon City in 2024 - Dewi Rostianingsih; Wiwit Desi Intarti; Siti Asiah (LPPM Universitas Bhamada Slawi PSDKU D III Kebidanan Kampus Kota Pekalongan, 2025)
Maternal health is measured by the Maternal Mortality Rate (MMR), where hypertension in pregnancy is one of the leading causes of maternal death worldwide. In 2020, approximately 302,000 maternal deaths were recorded in developing countries, some of which were caused by complications of hypertension. Approximately 10% of pregnancies globally are affected by hypertension, which can cause acute morbidity, long-term disability, and even maternal and infant death. Hypertension management is not only through pharmacological therapy, but also through non-pharmacological approaches such as upper back massage. This study aims to evaluate the effectiveness of upper back massage on reducing systolic and diastolic blood pressure in third-trimester pregnant women at Cilegon City Hospital in 2024. The study design used a quasi-experimental approach with a pretest-posttest approach without a control group and involved 25 respondents selected through purposive sampling. The results of the paired t-test showed a decrease in mean systolic pressure from 144 mmHg to 133 mmHg, and diastolic from 93 mmHg to 83 mmHg, with a significance value of p= 0.001 (p < 0.05). It can be concluded that upper back massage is effective in reducing blood pressure in pregnant women in the third trimester, so it can be used as a supporting intervention in the management of gestational hypertension.